Memristors with organic‐inorganic halide perovskites. Issue 2 (30th May 2019) - Zhao, Xiaoning; Xu, Haiyang; Wang, Zhongqiang; Lin, Ya; Liu, Yichun
Abstract: Organic‐inorganic halide perovskites (OHPs) have been intensively studied for application in solar cells with high conversion efficiency exceeding 22%. The unique electrical and optical properties of OHPs have led to their use in optoelectronic device applications beyond photovoltaics, such as light‐emitting diodes, photodetectors, transistors. New information storage technologies and computing architectures are being researched extensively with the aim of addressing the growing challenge of approaching end of Moore's law and von Neumann bottleneck. As the fourth basic circuit element, memristor is a leading candidate with powerful capabilities in information storage and neuromorphic computing applications. Recently, OHPs have received growing attention as promising materials for memristors. In particular, their mixed ionic‐electronic conduction ability paired with light sensitivity provide OHPs with the opportunity to display novel functions such as optical‐erase memory, optogenetics‐inspired synaptic functions, and light‐accelerated learning capability. This review covers recent advances in OHP‐based memristors development including memristive mechanism and analytical models, universal memristive characteristics for memory and neuromorphic computing applications, and novel multi‐functionalization. Challenges and future prospects of OHP‐based memristors are also discussed. Abstract : Organic‐inorganic halide perovskites (OHPs) have emerged as active materials for memristors. The recent significant developments of OHP‐based memristors are reviewed with a focus on the mechanism, models, memristive characteristics, and applications. The future challenges and prospects in developing OHP‐based memristors are also discussed.